The use of magnetic resonance imaging in the diagnosis of unilocular radiolucent images of the jawbone: a systematic review of the literature - Zaghden Olfa; Debré Timothé; Nguyen Thien Huong; Duong Lucas; Ferré François (Journal of Oral Medicine and Oral Surgery)
Introduction: Magnetic Resonance Imaging (MRI) is a recent and non-irradiating imaging technique allowing an optimal analysis of soft tissues. The goal of this review was to investigate the contribution of MRI in differentiating benign lesions of the jawbone presenting with the same appearance (radiolucent image) on panoramic radiograph, CT scan, or Cone Beam Computed Tomography (CBCT). Materials and methods: A literature review was performed on Medline and Embase. The MeSH keyword indexing language was used. The following keywords have been used. (Magnetic Resonance Imaging) AND ((odontogenic tumors) OR (ameloblastoma) OR (Cementoma) OR (odontogenic cyst, calcifying) OR (odontogenic tumor, squamous) OR (Odontoma) OR (Odontogenic cysts) OR (Basal cell nevus syndrome) OR (dentigerous cyst) OR (Odontogenic cyst, Calcifying) OR (Periodontal cyst)). This review was completed by a manual search in the bibliography of the selected articles. Results: A total of 220 articles were identified. After applying the non-inclusion criteria, 35 articles were retained for reading. After reading, 24 articles were included in data synthesis. MRI sequences including T1 weighted (T1w), T2 weighted (T2w) postcontrast T1 weighted with fat saturation (T1wFS+C) and diffusion-weighted images (DWI) may allow the operator to differentiate a cystic process from a tumor process. MRI can identify dentigerous cysts (DCs), inflammatory cysts, odontogenic keratocysts (OKs), or other unusual lesions, such as ameloblastoma (AB). A list of diagnostic criteria can therefore allow a more detailed analysis compared to CT or CBCT and establish a more accurate presumptive diagnosis. Discussion: MRI can allow a more precise orientation compared to CT scan analysis. The signal homogeneity on T1w and T2w, the postcontrast enhancement and the apparent diffusion coefficient are the three main parameters to be studied in order to make an accurate presumptive diagnosis. Conclusion: Based on this review, it can be concluded that the inclusion of MRI in the diagnosis process for unilocular radiolucent jaw lesions is beneficial for distinguishing between cystic and tumor process.